ANALISIS PRODUK DOMESTIK BRUTO MENURUT LAPANGAN USAHA DI PROVINSI KEPULAUAN RIAU TAHUN 2018-2020 - Dian Sabrina; Erika Gustian Fauzi; Salsabilah Sirait (Bajang Institute, 2022)
This study aims to determine the rate of GRDP growth according to business fields in Riau Islands Province. The secondary data used is period data in 2019-2021. This research method uses qualitative analysis, namely the method of collecting data by utilizing literature studies by looking for references from several sources. The results showed that the GRDP growth rate according to business fields in the Riau Islands Province decreased in almost all business sectors from year to year. Especially in 2020 due to the Covid-19 pandemic which resulted in the growth rate decreasing significantly.